Blade: undead by daylight ebook - Golden, Christopher (Blade: Undead By Daylight (2015)., 2015)
Collects Tomb of Dracula (1972) #10, 24, 58; Blade: Crescent City Blues #1. Relive the adventures of Marvel's half-vampire monster slayer — the man called Blade! In his deadly debut, Blade becomes immortal enemies with the biggest bloodsucker of all — Dracula himself! The stakes get higher when Blade's girlfriend is targeted by vampires! For Blade and Safron, love definitely hurts! Then, Blade heads to New Orleans to take on the city's new crime boss — one that just happens to be the vampire that killed his mother! Deacon Frost isn't the only thing giving Blade the blues — there's some bad Voodoo going down. Good thing Blade knows a Brother who can help with that! Get ready for Blade's sensational new series with four key stories that give you the lowdown on the Daywalker!